2015
DOI: 10.1371/journal.pone.0124859
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Enhances Cognitive Flexibility as Well as Astrocytic and Synaptic Markers in the Medial Prefrontal Cortex

Abstract: Physical exercise enhances a wide range of cognitive functions in humans. Running-induced cognitive enhancement has also been demonstrated in rodents but with a strong emphasis on tasks that require the hippocampus. Additionally, studies designed to identify mechanisms that underlie cognitive enhancement with physical exercise have focused on running-induced changes in neurons with little attention paid to such changes in astrocytes. To further our understanding of how the brain changes with physical exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…These exercise-evoked changes have been suggested to confer protection from stress-induced depletion of norepinephrine in the terminal fields (Dishman et al 2000). There is immense literature indicating that exercise improves learning, memory and cognitive flexibility (for example, (Barrientos et al 2011; van Praag et al 2005; Vaynman et al 2004; Brockett et al 2015)) as well as resilience to stress (Schoenfeld et al 2013) through changes in neurotransmitter systems other than the NA system or brain regions other than the cerebellum. We sought to provide complementary data by determining whether mild versus excessive voluntary wheel running activity (WRA) evoked different types of structural plasticity to the NA fibers in the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…These exercise-evoked changes have been suggested to confer protection from stress-induced depletion of norepinephrine in the terminal fields (Dishman et al 2000). There is immense literature indicating that exercise improves learning, memory and cognitive flexibility (for example, (Barrientos et al 2011; van Praag et al 2005; Vaynman et al 2004; Brockett et al 2015)) as well as resilience to stress (Schoenfeld et al 2013) through changes in neurotransmitter systems other than the NA system or brain regions other than the cerebellum. We sought to provide complementary data by determining whether mild versus excessive voluntary wheel running activity (WRA) evoked different types of structural plasticity to the NA fibers in the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…In the present report, we examined banked tissue from our prior study (Maynard and Leasure, 2013) in order to determine whether binge alcohol impacted exercise-induced cellular plasticity in the female brain. We focused on the medial prefrontal cortex (mPFC), a region that is both vulnerable to alcohol (Sullivan et al, 2000, Kubota et al, 2001, Sullivan and Pfefferbaum, 2005) and responsive to exercise (Mandyam et al, 2007, Brockett et al, 2015). In addition, the mPFC has connections to the hippocampus (Warburton and Brown, 2010, Varela et al, 2014), which we and others have shown to be damaged by binge alcohol (Nixon and Crews, 2002, 2004, Nixon et al, 2008, Maynard and Leasure, 2013).…”
mentioning
confidence: 99%
“…This indicates that there are other factors that affect the stability of the spine [36]. However, there has been considerable research showing that aerobic exercise can improve spatial memory capacity [10,11,37,38]. Quantitative measurements of PSD-95 may not describe adequately whether the spine with PSD-95 is a stable or functional spine able to support memory formation throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…One group of mice experienced the physical aerobic exercise treatment from 5-12 weeks (AK [5][6][7][8][9][10][11][12], and the other group was the control, tested at 12 weeks (K12). Mice were selected as the subjects for the experiment because mice are more active than rats.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation